Estimating tax capacity, tax effort and tax buoyancy for South Africa - Naape, Baneng Lucas (My University, 2019)
The main objective of this study is to assess South Africa’s tax revenue performance. This is achieved by estimating tax capacity and tax effort from 1960 - 2017 and tax buoyancy from 1995 - 2017. The study is unique in that, it tracks tax capacity, tax effort and tax buoyancy at an aggregate level for a particular country. The 2SLS results indicate that GDP per capita and inflation have a strong positive and statistically significant impact on revenue mobilisation while population growth, trade openness and agriculture share in GDP have a strong negative and statistically significant impact on revenue mobilisation. Furthermore, we find that South Africa’s tax effort index varies between 0.92 which is below capacity and 1.10 which is above capacity. On average, the tax effort index is 1.00, implying that South Africa performs well above its potential tax capacity. Notwithstanding, the tax system was also found to be fairly buoyant, although there is still room for improvement. The ARDL results indicate that VAT revenues and custom duties grow at a faster pace than the growth in final household consumption and import value, respectively. Total tax revenue growth, however, still falls behind as the estimated coefficient is below unity, implying that the growth in total tax revenues does not match the growth of the economy. Given these findings, we conclude that South Africa’s tax revenue performance has been fairly satisfactory over the period 1960 – 2017, albeit there is still room for improvement. For the government to generate value from the rapidly growing population, adequate investments in human capital and entrepreneurial skill development need to be made. The focus should be on broadening the tax base than on hiking already high tax rates.
A research report submitted in partial fulfilment of the requirements for the degree Master of Commerce in Economics in the Faculty of Commerce, Law and Management At the University of the Witwatersrand September 2019
Keywords: Tax revenue estimating; Taxation